On the quantum mechanical propagator for driven coupled harmonic oscillators - Dutra, Alvaro de Souza [UNESP] (IOP Publishing, 1992)
The exact propagator beyond and at caustics for a pair of coupled and driven oscillators with different frequencies and masses is calculated using the path-integral approach. The exact wavefunctions and energies are also presented. Finally the propagator is re-calculated through an alternative method, using the δfunction. © 1992 IOP Publishing Ltd.